An Ultrafast Fluorescent Probe for the Detection of Peroxynitrite in Living Cells - Xiaofeng Wang; Shu Xiao; Xuejun Zhou; Tingting Duan (Journal of Chemistry)
Peroxynitrite (ONOO−), a highly reactive nitrogen species, which plays a crucial role in numerous physiological and pathological processes of cell functionalization. The anomalous concentration of ONOO− may result in a range of diseases, such as arthritis, neurological disorders, and even cancer. Therefore, it is urgent to develop a simple and effective tool to monitor the fluctuation of ONOO− levels in biological systems. Herein, an ultrafast fluorescent probe (HND-ONOO) is proposed to detect ONOO−, which displays brilliant fluorescence in less than 30 s with a large Stokes shift. Furthermore, the probe exhibited the lower detection limit (48 nM) and satisfactory results in differentiating ONOO− from other related species. The probe that possesses good biocompatibility and low toxicity was employed to monitor the level of exogenous and endogenous ONOO− in living cells. Thus, the probe HND-ONOO could be served as a potential imaging tool to visualize intracellular ONOO− and understand the relationship between ONOO− and inflammation.